Seaweed biomass waste-derived carbon as an electrode material for supercapacitor - Jiang, L; Han, SOK; Pirie, M; Kim, HH; Seong, Y-H; Kim, H; Foord, JS (SAGE Publications, 2019)
Seaweed fibre is usually discarded as biomass waste after extraction of useful ingredients from seaweed. However this seaweed fibre, a natural abundant cellulose material with uniform dimensions 10 times smaller than other plant-based fibre can be utilized as electrode material for energy storage. In this work, we converted seaweed fibre into conductive carbon electrodes by a thermal carbonisation method. The morphology, chemical composition and conductivity are highly influenced by the carbonisation temperature. In comparison to other biomass sources such as cotton pulp, seaweed fibre is finer, smoother and more conductive at low carbonisation temperature. These carbonized seaweeds were then used as a supercapacitor, giving a high supercapacitance (226.3 Fg−1) at the carbonisation temperature of 900°C, and good stability within 2400 cycles. This specific capacitance is significantly higher than values obtained from filter paper or cotton pulp.